RESISTANCE OF DIFFERENT COTTON VARIETIES TO COTTON LEAF CURL VIRUS UNDER FIELD CONDITIONS - Aslam, Muhammad; Gilani, Atif Ali (Journal of Research (Science), 2000)
Nine cotton varieties (228/19, S-12, AC-134, MNH-440, MNH-410, MNH-295, MNH-395, MNH-329, and MNH-93) were evaluated for Cotton Leaf Curl Virus (CLCV) resistance. For CLCV, percent-infected plants were recorded on 62, 75, 82, 97, 104 and 114 days after planting (DAP). For whitefly, adults per leaf were counted on all these days expect 62 DAP. Difference in percent CLCV infected plants was non-significant among varieties on the first observation (62 DAP). From 75 to 114 DAP difference in percent infected plants was significant among the varieties tested. On 114 DAP, MNH-93 had the lowest infection (5.17%) followed by MNH-329 (9.93%). Highest infection was recorded in 228/19 (46.97%) and the second highest in S-12 (31.3%). Infection in other varieties was 18 to 28%. It was concluded that MNH-93 was resistant, MNH-329 moderately resistant, 228/19 highly susceptible and S-12 susceptible to CLCV. Whitefly, Bemisia tabaci (Genn.) population was not significantly different among varieties on any observation date, which indicates that response of the tested varieties to CLCV was independent of the whitefly population.